PTH-029 UGI cancers – are we looking?. (8th June 2018) - Goodoory, Vivek; Hodges, Lian; Crooks, Benjamin; Murgatroyd, Mark; White, Helen; Butler, Tom; Iqbal, Javaid
Abstract : Introduction: Oesophago-gastric (OG) cancers in the UK often present at an advanced stage, and hence reduced chance of curative therapy. A recent meta-analysis involving 3787 patients with OG cancer has shown that 11.3% OG cancers are missed at endoscopy 3 years before diagnosis. Recent guidelines from the BSG recommend that endoscopy units should audit for potential missed pathology in those diagnosed who have undergone an endoscopy in the preceding 3 years. Methods: This was a retrospective audit at a regional upper gastrointestinal centre reviewing all cases presenting with OG cancer over a 2 year period between Sept 2015 and Sept 2017. Data was collected from the electronic database, case notes and the GI reporting tool, in all patients to ascertain if an OGD was performed within 3 years prior to diagnosis. This included site of cancer, stage, endoscopist, probable reason for missed pathology and assessment of certain KPI's pertaining to the endoscopy. Results: 105 patients were diagnosed with OG cancers during this period. Median age 74 years; M:F 69:31; Oesophageal 60%:stomach 40%. Twenty-two patients (21%) had an OGD in the 3 years prior to their index (diagnostic) OGD; 11 (10.5%) were deemed 'not missed' cancers because there were valid reasons for repeating an endoscopy; and 11 (10.5%) were thought to represent 'missed' opportunities of diagnosing cancer in the preceding 3 years. The median time interval between the 1 st OGD and index OGD were 20 and 270 days for 'not-missed' and 'missed' groups respectively. Possible reasons for missed cancer were lack of lesion recognition (5/46%), dual pathology (1/9%), technical limitations of OGD (1/9%) or a combination of factors (4/36%). Adequacy of mucosal visualisation was not photo-documented in 64% of cases. The main reason for early repeat endoscopy in the 'non-missed' group was a high index of suspicion of pathology on initial OGD without any histological confirmation. Conclusions: A missed cancer rate of 10.5% in a regional upper GI centre is similar to published rates in a recent meta-analysis but does not achieve the minimal standard of <10% set by the BSG. These results were discussed at the EUGM and various measures being undertaken to reduce this include: modifications to optimise visualisation (simethicone pre-procedure), rigorous photo-documentation, dedicated surveillance lists eg. Barretts. This will be re-audited in 3 years.